Initiator protein dimerization plays a key role in replication control of Vibrio cholerae chromosome 2. Issue 16 (26th August 2014) - Jha, Jyoti K.; Ghirlando, Rodolfo; Chattoraj, Dhruba K.
Abstract: RctB, the initiator of replication of Vibrio cholerae chromosome 2 (chr2), binds to the origin of replication to specific 12-mer sites both as a monomer and a dimer. Binding to 12-mers is essential for initiation. The monomers also bind to a second kind of site, 39-mers, which inhibits initiation. Mutations in rctB that reduce dimer binding increase monomer binding to 12-mers but decrease monomer binding to 39-mers. The mechanism of this paradoxical binding behavior has been unclear. Using deletion and alanine substitution mutants of RctB, we have now localized to a 71 amino acid region residues important for binding to the two kinds of DNA sites and for RctB dimerization. We find that the dimerization domain overlaps with both the DNA binding domains, explaining how changes in the dimerization domain can alter both kinds of DNA binding. Moreover, dimerization-defective mutants could be initiation-defective without apparent DNA binding defect. These results suggest that dimerization might be important for initiation beyond its role in controlling DNA binding. The finding that determinants of crucial initiator functions reside in a small region makes the region an attractive target for anti- V. cholerae drugs.